Study of Synthesis and Performance of Clay and Clay-Manganese Monoliths for Mercury Ion Removal from Water - Aula Chairunnisak; Darmadi Darmadi; Adisalamun Adisalamun; Mukramah Yusuf; Syawaliah Mukhtar; Ulfa Rijal Safitri; Opie Azza Shafira (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
The pollution caused by mercury (Hg) is a matter of concern regarding worldwide ecosystems and public health. It is dangerous as it is highly poisonous and has more ways to get exposed than other heavy metal ions. Recently, the application of biomaterials with varying structures and designs for mercury adsorption has grown. In this research, clay monoliths (CM) and clay-manganese monoliths (CMM) were synthesized, investigated, and compared regarding their ability to adsorb mercury ions from water to determine the most effective adsorbents. CM and CMM were extruded through a stainless-steel molder with dimensions of 7 holes, 9 mm in radius, and 20 mm in height. The surface morphologies of both adsorbents were characterized using infrared (IR) spectroscopy and scanning electron microscopy (SEM). The effects of contact time (40, 80, 120, 160, 200, and 240 minutes) and initial concentrations (3–5 mg/L) were applied to evaluate both adsorption processes. The experiment was conducted in a batch reactor using a monolithic adsorbent that operated for 240 minutes. The experimental equilibrium data of the adsorption were examined with Langmuir and Freundlich models to find the best-fit isotherm. In the kinetic study, the pseudo-first-order was investigated in both linear and nonlinear models. The adsorption results showed that CMM had the highest adsorption efficiency (42.7%). The equilibrium study concluded that the Langmuir was the most significant isotherm model. The highest monolayer capacity and Langmuir constants (KL and aL) were 0.396, 1.329, and 0.396, respectively. The adsorption of both adsorbents was well displayed in the pseudo-first-order non-linear model. Experiments and processed data compromise the finding that CMM is more effective than CM at adsorbing mercury ions.